The vagabond class: shaping a criminal and political enemy in the French Revolution (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
The topic of this article is the cultural, social and political perception of vagrancy during the early years of the French Revolution. The argument put forward is that the Revolution was a defining context for the metamorphosis of the conception of vagabonds from anti-social individuals to a naturally criminal class hostile to both society and, most importantly, the State. The article analyses how between 1789 and 1792 vagabonds were progressively perceived as subversive individuals, as potential bandits. The text dwells on the analyses of vagrancy developed by some of the authorities of revolutionary France in addressing vagrancy as well as on the revolutionary and counter-revolutionary press. The aim is to highlight how this collective imaginary was universally internalised by contemporary actors, both supportive and opposed to the Revolution, and how this contributed to laying the foundations for shaping new political, cultural and social imaginaries.
Keywords: French revolution; vagabonds; brigands; citizenship; cultural imaginary